IMPROVING THE TRANSPORTATION IN BAGHDAD CITY CENTER - Alshammari, Lubna; Zuhair Mohamedmeki, Mohammed; Al-Mumaiz, Maha (Journal of Applied Engineering Science, 2025)
This study applies GIS techniques and users’ responses to evaluate potential traffic and hotspot congestion, by synthesizing a composite index based on scores for traffic potential and road density. The study reveals that Sheikh Omar, King Ghazi, Al-Rasheed, and Haifa Streets, are the most congested roads at Baghdad center. Due to the concentration of bridges in this area, that link city’s sides the passing traffic forming a pressure on roads leading to these bridges. Lacking sufficient parking spaces, enforced the users to park their vehicles on the road sides, which affected negatively on roads capacity. In addition to mixed land use, interference from pedestrians, and absence of systematic public transit all that contributed in magnifying the congestion problem at city center of Baghdad city. To address these challenges, the study proposed three strategies of improvements, immediate (0-1year), intermediate (1-3 years), and long term (+3 years). The immediate improvements comprised providing organized parking lots, enhance pedestrian and cycling infrastructure, and managing freight movements. Developed a systematic public transit system in and around city center, and applying the smart traffic management systems proposed as intermediate improvements. The long-term improvements covered developing the roads network of Baghdad city, land use and urban planning adjustments.
Keywords: traffic congestion, urban mobility, GIS-based analysis, land use and transportation, road density, sustainable mobility